Development of an Automatic Depth Control System for Underwater Vehicle - Muhamad Fadli, Ghani (2014)
This research explains on a design and development of an Automatic Depth Control System for underwater vehicle. This project shows the implementation's development of an Automatic Depth Control System on a test prototyping vehicle especially involved small-scale and low cost sub-sea robots